What Caused President Kennedys Wounds.? (London Journal of Medical and Health Research, 2024)
On November 22nd, 1963, President John F Kennedy was assassinated on Elm Street in Dallas TX and was pronounced dead at Parkland hospital at 1:00 PM (1).Within a week of Kennedy's death, the new President, Lyndon B. Johnson, created thePresident's Commission on the Assassination of President John F. Kennedy to investigate the deaths of both Kennedy and Lee Harvey Oswald the accused assassin (1).